Penerapan Mekanisme Transmisi Data ECG Berbasis Teknologi LoRa (Long Range) - Fadila Rafi Alifiandi; Eko Sakti Pramukantoro; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
In 2016, cardiovascular disease was the number one cause of death in the world. It was happened because cardiovascular disease was often detected late. The application of Internet of Things (IoT) in electrocardiogram (ECG) monitoring is considered as a solution to that problem. At this moment, an ECG monitoring system has been developed using IoT architecture. That system consists of ECG sensor nodes that use WiFi to transmit ECG data to the data storage on the cloud. However, WiFi is considered unsuitable to be used in IoT applications because of its large frame overhead and high power consumption. Therefore, a mechanism for transmitting ECG data based on LoRa technology, which is considered suitable because of its small frame overhead and low power consumption, is designed. This research produced a mechanism where sensor nodes are able to record and send ECG data to the LoRa gateway and LoRa gateway is able to forward received ECG data to the application on the cloud. However, the applied ECG data transmission mechanism in this research resulted 25,5 seconds end-to-end delay. So, it didn't fulfill the requirement in ECG data transmission for non-critical monitoring uses, the unfulfilled requirement is 4 seconds maximum delay.